Diffusion of the Balanced Scorecard: The Experience of a Sri Lankan Financial Institution - Gooneratne, T.N.; Wijesundara, G. (My University, 2016)
Over the past two decades various management accounting innovations, such as the balanced scorecard, activity-based costing, activity-based management and target costing have been diffused to organizations across the world. Although the merits of these tools and their application in various countries have been well researched, currently there is only limited understanding of how and why such tools get diffused in different organizational contexts. The purpose of this paper is to examine how and why the balanced scorecard has been diffused in a leading private sector financial institution in Sri Lanka. We adopt the qualitative methodology and the case study approach, and the data has been collected through in-depth interviews conducted with various managers and through documentary sources. The evidence gathered show that demand-side as well as supply-side forces have been significant in the diffusion of the balanced scorecard. This study makes an important contribution to the literature by offering a dynamic perspective on the diffusion of management accounting innovations, through a theoretical framework which brings together the supply-side as well as the demand-side forces into a single innovation diffusion model. The study also provides valuable insights for managers into the implementation and diffusion of management accounting tools such as the balanced scorecard.
Keywords: balanced scorecard; demand-side; diffusion; supply-side